Focal and Ambient Processing of Built Environments: Intellectual and Atmospheric Experiences of Architecture - Rooney, Kevin K.; Condia, Robert J.; Loschky, Lester C. (Frontiers in Psychology, 2017)
Neuroscience has well established that human vision divides into the central and peripheral fields of view. Central vision extends from the point of gaze (where we are looking) out to about 5° of visual angle (the width of one’s fist at arm’s length), while peripheral vision is the vast remainder of the visual field. These visual fields project to the parvo and magno ganglion cells, which process distinctly different types of information from the world around us and project that information to the ventral and dorsal visual streams respectively. Building on the dorsal/ventral stream dichotomy, we can further distinguish between focal processing of central vision, and ambient processing of peripheral vision. Thus, our visual processing of and attention to objects and scenes depends on how and where these stimuli fall on the retina. The built environment is no exception to these dependencies, specifically in terms of how focal object perception and ambient spatial perception create different types of experiences we have with built environments. We argue that these foundational mechanisms of the eye and the visual stream are limiting parameters of architectural experience. We hypothesize that people experience architecture in two basic ways based on these visual limitations; by intellectually assessing architecture consciously through focal object processing and assessing architecture in terms of atmosphere through pre-conscious ambient spatial processing. Furthermore, these separate ways of processing architectural stimuli operate in parallel throughout the visual perceptual system. Thus, a more comprehensive understanding of architecture must take into account that built environments are stimuli that are treated differently by focal and ambient vision, which enable intellectual analysis of architectural experience versus the experience of architectural atmosphere, respectively. We offer this theoretical model to help advance a more precise understanding of the experience of architecture, which can be tested through future experimentation.